Development of Online Islamic Medication Expert System (OIMES) - Daud, Hanita; Yahya, Noorhana; Low, Tan Jung (2009)
This paper presents an overview of the design and implementation of an online rule-based Expert Systems for Islamic medication. T his Online Islamic Medication Expert System (OIMES) focuses on physical illnesses only. Knowledge base of this Expert System contains exhaustively the types of illness together with their related cures or treatments/therapies, obtained exclusively from the Quran and Hadith. Extensive research and study are conducted to ensure that the Expert System is able to provide the most suitable treatment with reference to the relevant verses cited in Quran or Hadith. These verses come together with their related ‘actions’ (bodily actions/gestures or some acts) to be performed by the patient to treat a particular illness/sickness. These verses and the instructions for the ‘actions’ are to be displayed unambiguously on the computer screen. The online platform provides the advantage for patient getting treatment practically anytime and anywhere as long as the computer and Internet facility exist. Patient does not need to make appointment to see an expert for a therapy.